2021
DOI: 10.1016/j.csbj.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Vibrio sp. SP1 for the production of carotenoids directly from brown macroalgae

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In this host, previous studies indicated that the tacI promoter produced GFP upon activation with IPTG, while induction of the tet promoter resulted in low GFP yields (Tschirhart et al, 2019 ). The constitutive and inducible versions of the synthetic lac and tet promoters were evaluated in the pColE1‐derived plasmid with ~300 copies per cell (Tschirhart et al, 2019 ), except for the constitutive V2Lac , which was evaluated in pCloDF13‐derived vector with ~64 copies per cell in this strain (Park et al, 2021 ). The constitutive V2Lac (Figure 7Ai , green triangles) and V4Tc (Figure 7Bi , purple circles) promoters outperformed tacI (open squares) by ~16 and ~2‐fold respectively, while V3Lac (Figure 7Ai , blue diamonds ) , V1Tc (Figure 7Bi , red triangles) and V2Tc (Figure 7Bi , green triangles) produced similar levels as tacI .…”
Section: Resultsmentioning
confidence: 99%
“…In this host, previous studies indicated that the tacI promoter produced GFP upon activation with IPTG, while induction of the tet promoter resulted in low GFP yields (Tschirhart et al, 2019 ). The constitutive and inducible versions of the synthetic lac and tet promoters were evaluated in the pColE1‐derived plasmid with ~300 copies per cell (Tschirhart et al, 2019 ), except for the constitutive V2Lac , which was evaluated in pCloDF13‐derived vector with ~64 copies per cell in this strain (Park et al, 2021 ). The constitutive V2Lac (Figure 7Ai , green triangles) and V4Tc (Figure 7Bi , purple circles) promoters outperformed tacI (open squares) by ~16 and ~2‐fold respectively, while V3Lac (Figure 7Ai , blue diamonds ) , V1Tc (Figure 7Bi , red triangles) and V2Tc (Figure 7Bi , green triangles) produced similar levels as tacI .…”
Section: Resultsmentioning
confidence: 99%
“…In this host, previous studies indicated that the tacI promoter produced GFP upon activation with IPTG, while induction of the tet promoter resulted in low GFP yields [21]. The constitutive and inducible versions of the synthetic lac and tet promoters were evaluated in the pColE1 derived plasmid with ∼300 copies per cell [21], except for the constitutive V2Lac , which was evaluated in pCloDF13 derived vector with ∼64 copies per cell in this strain [42]. The constitutive V2Lac (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SP1 with brown algae as the substrate (2.98 mg/L) was approximately 6 times higher than that with P. atlantica T6c. 17 The high yield of β-carotene in Vibrio sp. SP1 could be due to the difference in construction of the β-carotene biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…dhg were reported as effective metabolic chassis for the bioconversion of brown algal feedstock into value-added chemicals. 17,18 However, none of these microbes were used for the deconstruction and metabolic conversion of red algal galactans such as agar and carrageenan. MHBs including Saccharophagus degradans 2−40, 19 Zobellia galactanivorans Dsij T , 20 Colwellia echini A3 T , 21,22 Pseudoalteromonas atlantica T6c, 23 and Paraglaciecola hydrolytica S66 T24 have been extensively studied for the deconstruction and metabolism of agar and carrageenan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation